2008
DOI: 10.1302/0301-620x.90b9.19891
|View full text |Cite
|
Sign up to set email alerts
|

Revision of metal-on-metal resurfacing arthroplasty of the hip

Abstract: We have reviewed 42 patients who had revision of metal-on-metal resurfacing procedures, mostly because of problems with the acetabular component. The revisions were carried out a mean of 26.2 months (1 to 76) after the initial operation and most of the patients (30) were female. Malpositioning of the acetabular component resulted in 27 revisions, mostly because of excessive abduction (mean 69.9 degrees ; 56 degrees to 98 degrees ) or insufficient or excessive anteversion. Seven patients had more than one reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
189
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(201 citation statements)
references
References 25 publications
10
189
0
2
Order By: Relevance
“…Previously, a few studies were directed at proper femoral component stem orientation in HRA [19,26,27]. However, it now appears proper placement of the acetabular component may be even more critical to the success of this procedure [8,9,11,21,30]. We investigated the value of using a single intraoperative portable crosstable AP radiograph to improve the accuracy of placing the acetabular component within a target range of inclination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, a few studies were directed at proper femoral component stem orientation in HRA [19,26,27]. However, it now appears proper placement of the acetabular component may be even more critical to the success of this procedure [8,9,11,21,30]. We investigated the value of using a single intraoperative portable crosstable AP radiograph to improve the accuracy of placing the acetabular component within a target range of inclination.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported revision rates of 1% to 5% at an average of 5 to 7 years in young and active patients after HRA [2,15,21,28]. Even though femoral neck fracture and femoral loosening were formerly reported as the most common failure modes in these studies [2,4,21], revision related to the acetabular component is being recognized more frequently in recent reports [8,11]. Previously, higher dislocation rates and increased wear rates were well-documented in standard THA with improper acetabular inclination angles [12,20,22,31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve articles remained after 198 articles were screened [4,11,12,18,24,28,30,34,38,43,44,48] (Fig. 3).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%